PENGARUH STRES KERJA, KOMUNIKASI, KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI DAMKAR PEMKO BATAM - Yandra Rivaldo; Dibyo Harits Sulaksono; Yandri Pratama; Supriadi (Postgraduate Management Journal, 2021)
The purpose of this study was to analyze the effect of job stress, communication, organizational commitment and motivation on job satisfaction. The population of this research is the Damkar Pemko Batam employees, amounting to 48 people. The sample consisted of 48 respondents, taken by the saturated sampling method. Data analysis uses multiple regression and hypothesis testing. The results of this study concluded that job stress variables significantly influence job satisfaction, communication variables significantly influence job satisfaction, organizational commitment variables significantly influence job satisfaction, motivation variables have a significant effect on job satisfaction. Variable work stress, communication, organizational commitment and motivation together have a significant effect on job satisfaction.